Accounting, identity, autopoiesis + sustainability: A comment, development and expansion on Lawrence, Botes, Collins and Roper (2013). Issue 1 (11th April 2016) - Khan, Tehmina; Gray, Rob
Abstract : Purpose: This paper is prompted by an analysis of accounting and accounting education by Lawrence et al. (2013) in this journal. In that paper, the authors use the theory of autopoiesis to articulate and explore, what they argue is, an inappropriate conservatism in accounting. This aims to develop the insights offered by Lawrence et al., to advance the understanding of autopoiesis and to use the insights from the theory of autopoiesis to try and confront (what we see as) the resistance shown in business and accounting to the possibilities of a more substantive sustainability agenda. Design/methodology/approach: The essay takes its departure point as the paper by Lawrence et al. and uses the theory of autopoiesis as a metaphorical lens through which to re-examine accounting, business and educational practice with respect to sustainability. Findings: This paper depart somewhat from Lawrence et al. 's arguments and inferences but broadly supports their contentions that accounting and accounting education are autopoietic. Some advances are offered to the theory and some issues for future research are briefly speculated upon. The analysis succeeds in highlighting that the accounting, business and educational systems may well be protecting their "cores" but are doing so by ignoring crucial and life-threatening information. In autopoietic terms, the sub-systems are behaving as closed systems that are causing self-harm and are being psychopathic. It is speculate that accounting educators may be, themselves, acting as autopoietic persons. Research limitations/implications: The essay, in identifying some of the empirical weaknesses inherent in the theory of autopoiesis in a social science context, suggests that the persuasiveness or otherwise of the theory will probably lie in the extent to which a reader finds the heuristic plausible and not in any easily testable propositions. The implications, if this limitation is accepted, are, broadly, that accounting and accounting education are acting psychopathically in the face of (arguably) life-threatening data. Practical Implications: There are extensive implications for research and policy but only those for education are explored here. Social Implications: If the analysis is persuasive, the implication for engagement with the exigencies of sustainability is profound and disturbing. Originality/value: The paper has two primary purposes: to challenge and develop debate around Lawrence et al. 's arguments and to use autopoiesis as one explanation for the inertia around sustainability, business and accounting. The paper extends the theory of autopoiesis as articulated in accounting to embrace both the issue of nesting systems and the autopoietic person. The combination of these contributions is combined with Lawrence et al., in offering a substantive challenge to accounting educators: albeit a substantively different one than those authors offered. It is these matters of difference that ultimately challenge the authors' roles as educators, researchers and accountants.